2019
DOI: 10.1088/1674-1056/28/5/057502
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and magnetocaloric effects in (Ho1−xYx)5Pd2 compounds*

Abstract: The crystal structure, magnetic and magnetocaloric properties of (Ho1−x Y x )5Pd2 (x = 0, 0.25, and 0.5) compounds are investigated. All the compounds crystallize in a cubic Dy5Pd2-type structure with the space group Fd3m and undergo a second order transition from spin glass (SG) state to paramagnetic (PM) state. The spin glass transition temperatures T g decrease from 26 K for x = 0 to 13 K for x = 0.5. In the PM region, the reciprocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…A number of reports suggested that metallic nanostructures with a specific morphology are of preference as spasing resonators with a low threshold gain. [37,[57][58][59][60][61][62][63][64][65] These studies generally determined the threshold gain by using the finite-element method or discrete dipole approximation to calculate absorption and scattering cross sections (referred to as σ abs and σ sca hereafter) of the core-shell spasing nanoparticle. The magnitudes of σ abs and σ sca will increase rapidly when the amount of gain is increased to a critical value and then decline with a further increase in the amount of gain.…”
Section: Reducing the Spasing Thresholdmentioning
confidence: 99%
“…A number of reports suggested that metallic nanostructures with a specific morphology are of preference as spasing resonators with a low threshold gain. [37,[57][58][59][60][61][62][63][64][65] These studies generally determined the threshold gain by using the finite-element method or discrete dipole approximation to calculate absorption and scattering cross sections (referred to as σ abs and σ sca hereafter) of the core-shell spasing nanoparticle. The magnitudes of σ abs and σ sca will increase rapidly when the amount of gain is increased to a critical value and then decline with a further increase in the amount of gain.…”
Section: Reducing the Spasing Thresholdmentioning
confidence: 99%
“…Comparatively, the pore size distribution range of Ni x Mn-LDO (x ¼ 4, 5, 6) was greatly reduced and more concentrated around 5-20 nm, which implies that the latter had a more uniform pore size structure. 43 Moreover, the surface area was obtained in Table 2 by calculating with BET method. Obviously, the surface area value of samples was sensitive to the proportion of Ni/Mn and displayed an upward trend from 41 to 83 m 2 g À1 with enhancement of Ni/Mn molar ratios.…”
Section: Results and Discussion Experimentalmentioning
confidence: 99%
“…44 The Ni 5 Mn-LDO catalyst presented a large specic surface area (70 m 2 g À1 ), suitable average pore diameter (9.35 nm) and pore volume (0.17 cm g À1 ), resulting in the desirable SCR activity. 43,45 3.2.5 NH 3 -TPD analysis. In NH 3 -SCR reaction, the adsorption and activation of NH 3 by catalyst is an important factor affecting the DeNO x action.…”
Section: Results and Discussion Experimentalmentioning
confidence: 99%
“…[14] The source profiles of vehicle and sea salt particles were also added. [20][21][22] The principle of CMB can be described by Equation (1), which assumes that each receptor concentration of a chemical species is composed of the linear sum of the products of the source profile species and source contributions. The effective variance solution was applied to calculate S j in Equation (1) by minimizing the weighted sums of the squares of the differences between the measured and calculated values of C i and F ij .…”
Section: Chemical Mass Balancementioning
confidence: 99%